POSTERIOR TRACTIONAL MEMBRANES FOLLOWING ANTI–VASCULAR ENDOTHELIAL GROWTH FACTOR FOR RETINOPATHY OF PREMATURITY. Issue Volume 16:Issues 5(2022) (September 2022) - Al-Khaled, Tala; Cole, Emily; Valikodath, Nita G.; Khanifar, Aziz A.; Johnson, Dina; Scripsema, Nicole K.; Chau, Felix Y.; Capone, Antonio; Chan, Robison Vernon Paul
Abstract : Two infants with Stage-3 retinopathy of prematurity developed tractional membranes after anti–vascular endothelial growth therapy. Surgical treatment was required to reduce the risk of poor visual outcomes secondary to tractional retinal detachment. These cases contribute to the literature assessing the outcomes of anti–vascular endothelial growth for retinopathy of prematurity management. Abstract : Purpose: To report two cases of tractional membrane formation following treatment with anti–vascular endothelial growth factor therapy in infants with Stage-3 retinopathy of prematurity. Methods: Retrospective review of electronic medical record for historical information, clinical examination documentation, and imaging from fundus photography, retinal ultrasonography, and fluorescein angiography. Results: Two patients with Stage-3 retinopathy of prematurity, previously treated with laser therapy and intravitreal bevacizumab, were referred to our institution for tractional membranes. The first case is of a male infant with Zone-II disease that progressed to Stage 4A with evidence of inferotemporal tractional retinal detachment only in the left eye. The second case is of a male infant with stable Zone-I disease with an epiretinal membrane in the left eye. Pars plicata vitrectomy and membranectomy were required for both cases because of the concern for subsequent tractional retinal detachment. Conclusion: Formation of tractional retinal membranes has been associated with anti–vascular endothelial growth factor therapy. These cases describe the formation of posterior tractional membranes after anti–vascular endothelial growth factor therapy. This potential ocular outcome should be considered when determining treatment plans for retinopathy of prematurity.